The Descriptive Narrative of the Ashurbanipal Relief Depicting His Fifth Campaign against Elam:: An Artistic Study - Hussein, Nabeel (مجلة دراسات في التاريخ والآثار, 2026)
This wall relief was discovered in the North Palace of the city of Nineveh. It consists of six wall panels, arranged in two groups of three on each side, forming frieze-like compositions. The panels depict a scene related to Ashurbanipal’s fifth military campaign against the land of Elam. The reliefs originally adorned the walls of Room (37) in the South-West Palace of King Sennacherib and portray a battle scene near the Ulai River, located on the western side of the entrance, as well as the death of the Elamite king Teumman.